2022
DOI: 10.3390/agronomy12102382
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Tomato Transpiration Cultivated in a Sunken Solar Greenhouse with the Penman-Monteith, Shuttleworth-Wallace and Priestley-Taylor Models in the North China Plain

Abstract: Tomato crops are increasingly cultivated in winter in solar greenhouses to achieve high economic benefit in the North China Plain (NCP). Accurate predictions of crop transpiration (Tr) are of great significance for formulating a scientific irrigation system and increasing water productivity in this water shortage region. In this study, tomato transpiration at daily and hourly scales were estimated using Penman-Monteith (PM), Shuttleworth-Wallace (SW), and Priestley-Taylor (PT) models, and results were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…When using the Priestley-Taylor model, the opposite trend was observed. The reasons for the latter could be the error accumulation in the performed long-range simulations that, in turn, could be caused by lower accuracy of the Priestley-Taylor model in water stress condition as reported in Shao et al (2022). In the case of the data collected in 2018, there was an overestimation of water intake according to the data of the two upper sensors located at depths of 0.1 m and 0.25 m (Figure 1).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…When using the Priestley-Taylor model, the opposite trend was observed. The reasons for the latter could be the error accumulation in the performed long-range simulations that, in turn, could be caused by lower accuracy of the Priestley-Taylor model in water stress condition as reported in Shao et al (2022). In the case of the data collected in 2018, there was an overestimation of water intake according to the data of the two upper sensors located at depths of 0.1 m and 0.25 m (Figure 1).…”
Section: Resultsmentioning
confidence: 92%
“…Thus, to quantify the intensity of evapotranspiration for more accurate modeling of moisture transport in the "soil-plantatmosphere" system, integrated models that consider soil and atmospheric physics along with plant physiology are needed (Overgaard et al, 2006). A widely used evapotranspiration model based on the Penman-Monteith equation (Monteith, 1965) successfully estimates it in the case of closed vegetation for various weather and soil conditions (see, e.g., Shao et al, 2022). In it, the processes of transpiration and evaporation from the bare soil, which are different intrinsically, are not considered separately.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there were few studies on the PT coefficient and its improved form in greenhouses. Shao et al (2022) [ 19 ] used the PT model to calculate the daily transpiration of tomatoes in a sunken heliostat in northern China and pointed out that the PT model had large errors when plants were subjected to high temperatures and water stress. Gong et al (2021) [ 20 ] also believed that the PT coefficient should be modified in combination with environmental changes due to the semi-closed characteristic of a greenhouse, whilst the ET of tomatoes in greenhouses was seriously underestimated by using the unimproved PT model.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies found that α was not only affected by the surrounding conditions, but also by other factors, such as plastic film coverage, canopy cover [ 18 ], soil available moisture [ 12 ] and leaf senescence [ 14 ]. Shao et al (2022) [ 19 ] used the PT model to calculate the daily transpiration of tomatoes in a sunken heliostat in northern China, and Gong et al (2021) [ 20 ] simulated the tomato ET in the solar greenhouse, indicating that establishing the α equation according to the environmental conditions was important. However, few studies have focused on this aspect in the greenhouse condition.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring transpiration on a time scale using weighing lysimeters or sap flow measurement takes more time and costs, so crop transpiration models are commonly adopted (Katsoulas and Stanghellini, 2019). The common models for predicting evapotranspiration and transpiration are Penman-Monteith (PM) (Allen et al, 1998), Shuttleworth-Wallace (SW) (Shuttleworth and Wallace, 1985), and Priestly-Taylor (PT) (Priestly and Taylor, 1972) models (Shao et al, 2022). PM is the most recommended worldwide standard method because it integrates energy, aerodynamic, and atmospheric parameters (Chia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%